FAKTOR YANG MEMENGARUHI KEPUASAN KEUANGAN PENGGUNA FINANCIAL TECHNOLOGY DI SURABAYA - ARMILIA, NADHIA; ISBANAH, YUYUN (Jurnal Ilmu Manajemen (JIM), 2019)
The existance of technology have made the growth of financial technology in Indonesia. People are aware of the use of financial technology that helps their mobility in managing finance. The aim of managing finances is to have a positive financial condition so they could achieve their financial satisfaction. Financial satisfaction of using financial technology is influenced by several factors. In this study the several factors are financial attitude, financial knowledge and financial behaviour. This study also determine the mediation effect of financial behavior on financial satisfaction. The sample in this study was 220 respondents of Surabaya society which is using a financial technology from range age 18-34 years. The analysis technique from this study is using Structural Equation Model (SEM) with AMOS 24 program. The results of this study indicate that financial attitude influences financial behavior, financial knowledge does not affect financial behavior, financial behavior influences financial satisaction, financial attitude does not affect on financial satisfaction , financial knowledge influences financial satisfaction, financial behaviour mediate financial attitude on financial behaviour, but financial behaviour does not mediate financial knowledge on financial satisfaction. Keywords: financial attitude; financial behaviour; financial knowledge; financial satisfaction.